Differentiating contributions of self-objectification and self-sexualization to young women's sexual agency. (September 2021) - Grower, Petal; Ward, L. Monique
Highlights: Body surveillance, a behavioral indicator of self-objectification, was associated with reduced sexual agency. Women who reported more enjoyment of sexualization also reported more entitlement to sexual pleasure and sexual self-esteem. Women's enjoyment of sexualization was unrelated to their sexual assertiveness, satisfaction, and condom use self-efficacy. Abstract: Findings consistently illustrate the negative association between women's sexual objectification and their sexual functioning. At the same time, some scholars argue that sexualized self-presentation may be a way to embrace one's sexuality and may signify empowerment. To date, no studies have explicitly explored the potential differential contributions of self-objectification and self-sexualization to multiple aspects of women's sexual agency. Towards this end, we surveyed 556 undergraduate women to examine how body surveillance, self-objectification, and self-sexualization differentially predict women's sexual assertiveness, sexual satisfaction, feelings of entitlement to sexual pleasure, condom use self-efficacy, and sexual esteem. Path analysis demonstrated consistent negative links between body surveillance, one behavioral manifestation of self-objectification, and sexual agency outcomes, but revealed both negative and positive links between measures of sexualization and sexual agency. This complex set of associations highlights the value of studying self-objectification and self-sexualization both in tandem and separately, so that researchers can develop a better understanding of the implications of each for women's sexual agency.